Site-specific mesenchymal control of inflammatory pain to yeast challenge in vulvodynia-afflicted and pain-free women. Issue 3 (March 2015) - Foster, David C.; Falsetta, Megan L.; Woeller, Collynn F.; Pollock, Stephen J.; Song, Kunchang; Bonham, Adrienne; Haidaris, Constantine G.; Stodgell, Chris J.; Messing, Susan P.; Iadarola, Michael; Phipps, Richard P.
Abstract : Abstract: Fibroblast strains were derived from 2 regions of the lower genital tract of localized provoked vulvodynia (LPV) cases and pain-free controls. Sixteen strains were derived from 4 cases and 4 controls, age and race matched, after presampling mechanical pain threshold assessments. Strains were challenged with 6 separate stimuli: live yeast species ( Candida albicans, Candida glabrata, Candida tropicalis, and Saccharomyces cerevisiae ), yeast extract (zymosan), or inactive vehicle. Production of prostaglandin E2 (PGE2 ) and interleukin 6 (IL-6) were proinflammatory response measures. Highest IL-6 and PGE2 occurred with vestibular strains after C albicans, C glabrata, and zymosan challenges, resulting in the ability to significantly predict IL-6 and PGE2 production by genital tract location. After C albicans and C glabrata challenge of all 16 fibroblast strains, adjusting for dual sampling of subjects, PGE2 and IL-6 production significantly predicted the presampling pain threshold from the genital tract site of sampling. At the same location of pain assessment and fibroblast sampling, in situ immunohistochemical (IHC)(+) fibroblasts for IL-6 and Cox-2 were quantified microscopically. The correlation between IL-6 production and IL-6 IHC(+) was statistically significant; however, biological significance is unknown because of the small number of IHC(+) IL-6 fibroblasts identified. A low fibroblast IL-6 IHC(+) count may result from most IL-6 produced by fibroblasts existing in a secreted extracellular state. Enhanced, site-specific, innate immune responsiveness to yeast pathogens by fibroblasts may be an early step in LPV pathogenesis. Fibroblast strain testing may offer an attractive and objective marker of LPV pathology in women with vulvodynia of inflammatory origin. Abstract : Site-specific fibroblasts produce IL-6 and PGE2 that predict in situ pain threshold and characterize site-specific allodynia of localized provoked vulvodynia.